Hubungan Asupan Zat Gizi Makro (Energi, Protein, Lemak, Karbohidrat) terhadap Status Gizi Pasien Gagal Ginjal Kronik Rawat Jalan dengan Hemodialisis di RSUD dr. Moewardi - Kusumastuti, Widya Reza, Ririn Yuliati S.Si.T., M.Si, dr Listiana Masyita Dewi, M. Sc (2015)
Introduction : The most used replacement therapy for chronic renal failure patients in Indonesia is hemodialysis. Hemodialysis in patients with chronic renal failure has impacts, including a decrease in food intake that can cause malnutrition in patients. Objective : The purpose of this research was to asses the correlations between macro nutrient intakes and nutritional status of chronic renal failure with hemodialysis outpatients at dr. Moewardi State Hospital. Research Method : This research used analytic observational with cross-sectional design. The respondents were selected through by consecutive sampling method. There were 46 chronic renal failure patients participated in this study. Nutritional status data were obtained through Body Mass Index measurements, macro nutrient intake data were obtained using 24 hour food recall form. Result : Most patients had poor energy, protein, fat, and carbohydrate intakes which were 41 patients (89,1%), 40 patients (87%), 40 patients (87%), and 43 patients (93,5%), respectively. There was not any correlation between nutritional status and intakes of energy (p=0,163), protein (p=1,000), fat (p=0,390), and carbohydrate (p=0,585). Conclusion : There was not any correlation between macro nutrient intakes and nutritional status of chronic renal failure with hemodialysis outpatients ar dr. Moewardi State Hospital. Further research needs to be done with due regard to all factors that may affect the incidence of malnutrition in chronic renal failure with hemodialysis patients. Keywords : chronic renal failure, macro nutrient intake, nutritional status Bibliography : 51 : 1990-2013